Fangelønn og menneskeverdighet - Knut Papendorf (Nordisk Tidsskrift for Kriminalvidenskab)
The German Constitutional Court has recently ruled on the issue of prisoner wages, which will lead to a more equitable pay scale. German prisoners are currently paid approximately 10 DM per day, or 5% of the average non-prison wage. The Court found this unconstitutional since work in prison, as the central part of the rehabilitative aim, should reflect the principle of fair salary. The ruling was based on constitutional principles regarding the social state and the dignity of all human beings.